İNVAZİV ASPERGİLLOZUN ÖN TANIMINDA GALAKTOMANNAN ANTİJENİNİ BELİRLEMENİN YERİ VE ÖNEMİ - KANTARCIOĞLU, A. Serda; YÜCEL, Ayhan (Cerrahpaşa Medical Journal, 2014)
Background and Design.- The precise diagnosis of invasive aspergillosis depends upon demonstrating the presence of Aspergilli by direct microscopical examination and isolating the fungus from specimens obtained from a sterile site. However, invasive procedures are often precluded by cytopenia or by the critical condition of the patient. Hence, definite diagnosis is infrequently made before fungal proliferation becomes overwhelming and therapy may no longer be successful. Galactomannan, an exo-antigen, is a major cell wall constituent released during growth. The detection of circulating galactomannan in the serum, bronchoalveolar lavage and other body fluids together with the findings obtained by computed tomographic (CT) scanning of the chest contributes to the early presumptive diagnosis of invasive aspergillosis. Today, in mycology, a more targetted “pre-emptive” therapy directed towards the high-risk patients and based upon a battery of clinical, radiological and microbiological data that suspect the presence of invasive aspergillosis has being replaced to empirical therapy. Galacromannan (GM) can be detected by latex agglutination or enzyme immunoassay tests. GM positivity with careful interpretation, in combination with CT-scanning or radiology appears highly useful for early presumptive diagnosis of invasive aspergillosis and sufficiently predictive to start pre-emptive therapy. This paper reviews the relevant literature to clarify the significance of GM detection in invasive aspergillosis.